Isolated Congenital Diaphragmatic Hernia in the Third Trimester: a Case Report and Literature Review - Chun-Chieh Chia; Soon-Cen Huang; Chun-Hui Chang (Taiwanese Journal of Obstetrics & Gynecology, 2006)
Objective: To report a rare congenital anomaly, a right diaphragmatic hernia, in a near-term baby Case Report: A 40-year-old female, gravida 3, para 2, had undergone regular prenatal care in our department since the early second trimester. She underwent amniocentesis at 16 weeks of gestation. The result showed normal 46,XY. Fetal growth was appropriate throughout the pregnancy. A small heart with marked left-side deviation was noted in the third trimester. The heart rate was less than 25% of normal. A homogenous mass with centralized vessels was noted in the fetus's right chest. The baby showed respiratory distress immediately after delivery. Imaging studies after birth proved there was a right diaphragmatic hernia with severe pulmonary hypertension and poor lung function. Conclusion: Right congenital diaphragmatic hernia is rare. A prenatal diagnosis is difficult to make in the second trimester. Prognosis is greatly influenced by the associated abnormalities.